The association of ZIC5 gene rs965623242 polymorphism with neural tube defects - Onalan, Ebru; Askin, Yasemin; Kaymaz, Tugce; Saracoglu, Mehmet; Kazez, Ahmet; Suzek, Tugba O. N. A. L.; Konar, Vahit (Marmara Univ, Fac Medicine, 2024)
Objective: This study aims to evaluate the effects of the rs965623242 reference single nucleotide polymorphism (SNP) on the ZIC5 gene in patients with neural tube defect (NTD). Patients and Methods: One hundred sixty-eight controls and one hundred sixty-eight NTD patients were included in the study. Deoxyribonucleic acid (DNA) isolation from peripheral blood samples was carried out for all participants. rs965623242 polymorphic region was amplified by polymerase chain reaction (PCR) and then sequenced. Results: In the 5' untranslated region (UTR) of the first exon, guanine (G) to adenine (A) base change was detected in the 38th base of NM_033132.5. G to A base change was determined as GG genotype in 117 (69.6%), AG genotype in 30 (17.86%), and AA genotype in 21 (12.5%) patients. In the control group, GG genotype in 107 (63.7%), AG genotype in 23 (13.7%) and AA genotype in 38 (22.7%) were observed. The statistically significant difference was observed between the NTD and the control groups in ZIC5 genotypes or allele frequencies [p=0.044, odds ratio (OR)=0.49 (0.27-0.88) and p=0.021, OR=0.65 (0.46-0.93), respectively]. Conclusion: ZIC5 rs965623242 polymorphism may have a protective role in the NTD development in the Eastern Anatolian population, in Turkey. Although, these findings demonstrate that the rs965623242 polymorphism is associated with NTD, we do not clarify how its expression is affected during the embryonic period and ongoing processes. We will need advanced ongoing genetic and clinical studies to obtain more detail.
Keywords: Congenital anomalies; Neural tube defect; Spina bifida; ZIC5 gene; Polymorphism